2021
DOI: 10.1177/09544062211027203
|View full text |Cite
|
Sign up to set email alerts
|

An improved contact model considered the effect of boundary lubrication regime on piston ring-liner contact for the two-stroke marine engines from the perspective of the Stribeck curve

Abstract: The prediction of lubrication performance is required to be the basement of friction optimization for marine engines. This paper simulates the lubrication performance of marine engines based on statistical models which have the advantages of fast, efficient, and macroscopic fault location. Boundary lubrication exists in the piston ring-cylinder liner (PRCL) of two-stroke marine engines because of the harsher load, lower speed, and larger structure. It has been proposed that there would be tribofilm under bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To investigate the effect of roughness on lubrication, the average Reynolds equation was developed (Patir and Cheng, 1978). This approach has been widely used in the investigation of ring-liner lubrication (Khan et al , 2021; Li et al , 2021; Lyu et al , 2022). Homogenization technology was used to investigate the effects a of honing texture (Spencer et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effect of roughness on lubrication, the average Reynolds equation was developed (Patir and Cheng, 1978). This approach has been widely used in the investigation of ring-liner lubrication (Khan et al , 2021; Li et al , 2021; Lyu et al , 2022). Homogenization technology was used to investigate the effects a of honing texture (Spencer et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Garcia et al 23 showed and experimentally verified that by surface texturing 25% and 5% reduction in asperity contact force and total friction force can be achieved. Xiuyi et al 24 proposed an improved contact model for analysis of tribological performance of PRCLC from the perspective of Stribeck curve. They concluded that there is a tribofilm growth in boundary lubrication regime and that directly relates with asperity contact pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Concludingly, an X-ray photoelectron spectroscopy (XPS) or electron energy loss spectroscopy (EELS)-analysis with the worn specimen surfaces coupled with molecular dynamic simulations could be carried out. Furthermore, advanced friction models could be used, e.g., as proposed by Xiuyi et al [59], to improve the predictability of friction in the case of occurring tribofilm formation and removal.…”
mentioning
confidence: 99%